Channelrhodopsin-1 phosphorylation changes with phototactic behavior and responds to physiological stimuli in Chlamydomonas. - Böhm, Michaela; Boness, David; Fantisch, Elisabeth; Erhard, Hanna; Frauenholz, Julia; Kowalzyk, Zarah; Marcinkowski, Nadin; Kateriya, Suneel; Hegemann, Peter; Kreimer, Georg (The Plant Cell, 2019)
The unicellular alga Chlamydomonas reinhardtii exhibits oriented movement responses (phototaxis) to light over more than three log units of intensity. Phototaxis thus depends on the cell's ability to adjust the sensitivity of the involved photoreceptors to the ambient light conditions. In C. reinhardtii these are the channelrhodopsins ChR1 and ChR2, which are plasma membrane located light-gated cation channels. Although ChRs are widely used in optogenetic studies, knowledge about ChR signaling in alga is still limited. We characterized the in vivo phosphorylation of ChR1. Its reversible phosphorylation occurred within seconds as a graded response to changes in the light intensity and ionic composition of the medium and depended on an elevated cytosolic Ca2+ concentration. Changes in the phototactic sign were accompanied by alterations in the ChR1 phosphorylation status. Furthermore, compared with the wild-type, a permanently negative phototactic mutant required higher light intensities to evoke ChR1 phosphorylation. C-terminal ChR1 truncation disturbed the reversible phosphorylation, whereas it was normal in ChR2-knockout and eyespot-assembly mutants. Newly identified phosphosites in regions important for ChR1 function point to their potential regulatory role(s). We propose that multiple ChR1 phosphorylation, regulated via a Ca2+-based feedback loop, is one important component in the adaptation of phototactic sensitivity in Chlamydomonas.

Insights into degradation and targeting of the photoreceptor channelrhodopsin-1 - Wolfram, Michaela; Greif, Arne; Baidukova, Olga; Voll, Hildegard; Tauber, Sandra; Lindacher, Jana; Hegemann, Peter; Kreimer, Georg (Plant Cell and Environment, 2024)
In Chlamydomonas, the directly light-gated, plasma membrane-localized cation channels channelrhodopsins ChR1 and ChR2 are the primary photoreceptors for phototaxis. Their targeting and abundance is essential for optimal movement responses. However, our knowledge how Chlamydomonas achieves this is still at its infancy. Here we show that ChR1 internalization occurs via light-stimulated endocytosis. Prior or during endocytosis ChR1 is modified and forms high molecular mass complexes. These are the solely detectable ChR1 forms in extracellular vesicles and their abundance therein dynamically changes upon illumination. The ChR1-containing extracellular vesicles are secreted via the plasma membrane and/or the ciliary base. In line with this, ciliogenesis mutants exhibit increased ChR1 degradation rates. Further, we establish involvement of the cysteine protease CEP1, a member of the papain-type C1A subfamily. ΔCEP1-knockout strains lack light-induced ChR1 degradation, whereas ChR2 degradation was unaffected. Low light stimulates CEP1 expression, which is regulated via phototropin, a SPA1 E3 ubiquitin ligase and cyclic AMP. Further, mutant and inhibitor analyses revealed involvement of the small GTPase ARL11 and SUMOylation in ChR1 targeting to the eyespot and cilia. Our study thus defines the degradation pathway of this central photoreceptor of Chlamydomonas and identifies novel elements involved in its homoeostasis and targeting.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ARL11; Calpain; CEP1; Chlamydomonas; cilia; cysteine proteases; extracellular vesicles; photoreceptor endocytosis; phototaxis; phototropin

Multifactorial in vivo regulation of the photoreceptor channelrhodopsin-1 abundance. - Wolfram, Michaela; Greif, Arne; Sizova, Irina; Baidukova, Olga; Hegemann, Peter; Kreimer, Georg (Plant Cell and Environment, 2023)
Oriented movement (phototaxis) is an efficient way to optimize light-driven processes and to avoid photodamage for motile algae. In Chlamydomonas the receptors for phototaxis are the channelrhodopsins ChR1 and ChR2. Both are directly light-gated, plasma membrane-localized cation channels. To optimally adjust its overall light-dependent responses, Chlamydomonas must tightly control the ChRs cellular abundance and integrate their activities into its general photoprotective network. How this is achieved is largely unknown. Here we show that the ChR1 protein level decreases upon illumination in a light-intensity and quality-dependent manner, whereas it is stable in prolonged darkness. Analysis of knockout strains of six major photoreceptors absorbing in the blue-violet range, which is most effective in evoking ChR1 degradation, revealed that only phototropin (PHOT) is involved. Notably, ChR2 degradation was normal in a ΔPHOT strain. Further, our results indicate that a COP1-SPA1 E3 ubiquitin ligase, the transcription factor Hy5 as well as changes in the cellular redox poise and cyclic nucleotide levels are additional components involved in this light acclimation response of Chlamydomonas. Our data highlight the presence of an adaptive framework connecting phototaxis with general photoprotective mechanisms via the use of overlapping signaling components already at the level of the primary photoreceptor.

Orient in the World with a Single Eye: The Green Algal Eyespot and Phototaxis - Böhm, Michaela; Kreimer, Georg (Progress in Botany, 2020)
Motile algae exhibit well-defined movement responses toward or away from a light source, known as positive and negative phototaxis, respectively. To optimize this essential behavior, algae often possess a complex directional optical device, the eyespot. Interest in eyespots has increased considerably during the last decade due to their elaborate ultrastructure and the presence of unique photoreceptors. The latter form an important basis for ongoing developments of optogenetic tools in the field of neurobiology and cell biology. Green algal eyespots, especially that of Chlamydomonas reinhardtii P. A. Dangeard, are the best studied with respect to their biophysical function, assembly, positioning, and signaling cascade(s) finally leading to the oriented movement. Here we give a short general introduction to the eyespot and the phototactic orientation of this algal group and summarize recent progress in the diverse eyespot-related areas. We also address emerging novel insights in the homeostatic feedback regulation of phototactic sensitivity by the cells’ physiological activities.<br